2012
DOI: 10.1186/1475-2891-11-78
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week double-blind randomized clinical trial of vitamin D3supplementation on body fat mass in healthy overweight and obese women

Abstract: BackgroundVitamin D concentrations are linked to body composition indices, particularly body fat mass. Relationships between hypovitaminosis D and obesity, described by both BMI and waist circumference, have been mentioned. We have investigated the effect of a 12-week vitamin D3 supplementation on anthropometric indices in healthy overweight and obese women.MethodsIn a double-blind, randomized, placebo-controlled, parallel-group trial, seventy-seven participants (age 38±8.1 years, BMI 29.8±4.1 kg/m2) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(84 citation statements)
references
References 41 publications
(45 reference statements)
4
74
1
2
Order By: Relevance
“…The effects of vitamin D3 on the reduction of waist circumference is also reported in a study by Salehpour et al (5). In addition, other studies such as Tamer et al have found that waist circumference and waist-hip ratio have a negative relationship with the serum level of vitamin D3 (12).…”
Section: Discussionsupporting
confidence: 53%
“…The effects of vitamin D3 on the reduction of waist circumference is also reported in a study by Salehpour et al (5). In addition, other studies such as Tamer et al have found that waist circumference and waist-hip ratio have a negative relationship with the serum level of vitamin D3 (12).…”
Section: Discussionsupporting
confidence: 53%
“…25,26 Choice of adiposity measures may be important in the evaluation of relationships between vitamin D supplementation and adiposity. 27 Only a few trials of vitamin D have assessed changes in body composition or in visceral or other fat depots, as directly measured by DXA, 23,28,29 magnetic resonance imaging (MRI), or computed tomography (CT). 30,31 DXA provides measures of overall adiposity, lean tissue, and regional distributions, with good reproducibility and minimal radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…3,[11][12][13][14][15][16] It is not clear whether the VDD is produced by obesity or obesity is a consequence of VDD, 17 because obese individuals specially women, 18 are susceptible to VDD due to diminished availability of VD stored in the adipose tissue, and on the other hand, 18 some studies in obese individuals suggest that the supplementation with VD reduces the body fat mass. [19][20][21] Women at reproductive age are a group that can be intervened at earlier age for VDD and its long term complications.VDD during adulthood increases the risk of osteopenia, osteoporosis, muscle weakness, osteomalasia and pathological fractures and can worsen other chronic conditions, such as the polycystic ovary syndrome; it also is a risk factor for cardiovascular diseases, metabolic syndrome, some types of cancer and some autoimmune diseases. [16][17][18][19][20][21][22][23][24] This study aims to describe the prevalence of VDD and VDI, and the dietary sources of VD, in a probabilistic sample of women at reproductive age participating in Ensanut-2012, stratified by sociodemographic factors and BMI categories.…”
Section: Vitamin D Status In Mexican Womenmentioning
confidence: 99%
“…[19][20][21] Women at reproductive age are a group that can be intervened at earlier age for VDD and its long term complications.VDD during adulthood increases the risk of osteopenia, osteoporosis, muscle weakness, osteomalasia and pathological fractures and can worsen other chronic conditions, such as the polycystic ovary syndrome; it also is a risk factor for cardiovascular diseases, metabolic syndrome, some types of cancer and some autoimmune diseases. [16][17][18][19][20][21][22][23][24] This study aims to describe the prevalence of VDD and VDI, and the dietary sources of VD, in a probabilistic sample of women at reproductive age participating in Ensanut-2012, stratified by sociodemographic factors and BMI categories.…”
Section: Vitamin D Status In Mexican Womenmentioning
confidence: 99%